2020
DOI: 10.3341/kjo.2019.0133
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Ocular Surface Parameters with Subjective Symptom Severity in Dry Eye Disease

Abstract: To evaluate the clinical symptoms of patients with dry eyes, based on the ocular surface disease index (OSDI) and analyze the relationship between OSDI and various ocular surface parameters. Methods: This was a retrospective study that included 45 eyes of 45 dry eye patients who visited the Seoul Nune Eye Hospital from August 2017 to December 2017. The patients were assessed by non-invasive keratography for the first break-up time, lipid layer thickness (LLT), tear osmolarity, tear matrix metalloproteinase-9 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…The tear film consists of two phases, a lipid layer overlying a muco-aqueous layer [3]. Tear lipids secreted from the meibomian glands (MG) aids the tear film maintaining its solidity [4]. Meibomian gland dysfunction (MGD), the main cause of evaporative dry eye, is more frequent than aqueous-deficient dry eye [5].…”
Section: Introductionmentioning
confidence: 99%
“…The tear film consists of two phases, a lipid layer overlying a muco-aqueous layer [3]. Tear lipids secreted from the meibomian glands (MG) aids the tear film maintaining its solidity [4]. Meibomian gland dysfunction (MGD), the main cause of evaporative dry eye, is more frequent than aqueous-deficient dry eye [5].…”
Section: Introductionmentioning
confidence: 99%
“… 43–46 However Lee et al found a correlation between OSDI and NIKBUT for the first breakup time (r= −0.33) and lipid layer thickness (LLT, r= −0.42). 47 Also, Blackie et al reported that LLT was significantly correlated with severe symptoms using the SPEED questionnaire. 48 Due to the low correlation coefficients in both Lee et al, Blackie et al, and our study, the clinical utility of the correlations is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that noninvasive examinations, such as noninvasive keratograph break-up time and interferometry of LLT, could be efficient tools for evaluating dry eye symptoms. 28 …”
Section: Discussionmentioning
confidence: 99%